Vertically-aligned silicon carbide nanowires as visible-light-driven photocatalysts - Hong, J; Meysami, S; Babenko, V; Huang, C; Luanwuthi, S; Acapulco, J; Holdway, P; Grant, P; Grobert, N (Elsevier, 2017)
Vertically-aligned crystalline silicon carbide nanowires (VASiCs) (1 mm long and 50–90 nm in diameter) were synthesised in gram scale using SiO2-infiltrated vertically-aligned multi-wall carbon nanotubes (VACNTs) and Si powder. In situ residual gas analysis was employed to study their formation and revealed CO to be the main by-product during synthesis. The in situ studies also showed that the formation of VASiCs begins at 1150 °C with the growth rate reaching a maximum at 1350 °C. A possible growth mechanism was established based on both, in situ and ex situ characterisation. The VASiCs have an estimated band gap of 2.15 eV, are photocatalytically active, and show strong light absorbance of up to 577 nm. Under UV-visible light (260–800 nm) as grown VASiCs could remove 90% Rhodamine B (RhB) within 30 min. Over period of 4 hours under visible light (400–800 nm) more than 95% RhB was removed demonstrating their potential as visible-light-driven photocatalysts.